Locating the "Digital" in Digital Journalism Studies: Transformations in Research. Issue 3 (16th March 2019) - Robinson, Sue; Lewis, Seth C.; Carlson, Matt
Abstract: This essay applies six commitments for journalism studies to research involving digital technologies, namely: contextual sensitivity, holistic relationality, comparative inclination, normative awareness, embedded communicative power, and methodological pluralism. We argue that the emergent characteristics of digital journalism – as reflected in algorithms, automation, networking tools, and mass posting, sharing, and production with a click of a button – bring on transformations that must be theorized holistically, contextually, and relationally as part of a subfield of journalism studies called "digital journalism studies." Spatial and temporal considerations inform this argument and complicate how the field of journalism studies examines news production and consumption. It is within the studies of "transformation" that we as researchers find an emergent theory that not only reveals the disruption of norms and introduction of new developments, but also exposes enduring power dynamics. By locating the "digital" in digital journalism studies through the lens of these six commitments, scholars can better identify evolving and blurring boundaries of news content and its production, distribution, and consumption processes.